Characterization of Chilli leaf curl virus - ., Ahmed; Sharma, Abhishek; Zehra, Syed Berjes; Kang, S S (Indian Journal of Plant Protection, 2020)
Twelve symptomatic chilli samples showing variable leaf curl symptoms resembling to those caused by begomovirus were collected from chilli fields of Vegetable Research Farm, Department of Vegetable Sciences, Punjab Agricultural University, Ludhiana and checked for the association of begomovirus using PCR based detection method. Once the samples were found positive for begomovirus presence, the same set of samples were further used as template using virus species Tomato leaf curl Palampur virus (ToLCPV), Tomato leaf curl New Delhi virus (ToLCNDV), Tomato leaf curl Karnataka virus (ToLCKV), specific primers as well DNA-B and DNA-Î² primers. The samples (C1 and C4), which were not amplified by universal degenerated primers as well as species specific primers were subjected to RCA (Rolling circle amplification) followed by PCR using begomovirus specific AV494/AC1048 primers for partial characterization. In sample number C3 and C9, mixed infection of two virus species i.e., ToLCPV and ToLCNDV was observed. In six samples viz., C2, C8 and C11 ToLCKV and in samples viz., C7, C10 and C12, ToLCPV along with beta satellite molecules were found to be associated. Similarly, in sample C6, a bipartite ToLCNDV with beta satellite was detected. In sample C5, ToLCPV alone was detected. In both chilli samples (C1 and C4), the expected size amplicon (~575 bp) from core CP region was observed, eluted and cloned in plasmid vector pTZ57R/T. Phylogenetic analysis, based on partial genomic DNA sequences, revealed that the two viruses clustered in different clades. Chilli clone1.1 shared a close common ancestor with Papaya leaf crumple virus, forming a subclade that is distantly related to other begomoviruses used for analysis. Similarly, chilli clone 4.1 shared a close common ancestor with recently described Tomato leaf curl Joydebpur virus and formed a separate subclade. Further attempts were made to clone the full-length genome of both the samples C1 and C4. The results were further confirmed with AV494/AC1048 primers showing amplification of 575bp fragment from same clone.